Peningkatan Kemampuan Membaca Ordinal Number dengan Menggunakan Bola-Bola Hypnotist dalam 5M - Zaimatun Zaimatun (Jurnal Didaktika Pendidikan Dasar, 2021)
The aims of using Hypnotist balls in 5M is to increase the students’ ordinal number reading competency and students’ activeness in the learning process. Hypnotist balls is a hypnoteaching communication medium implementation. While, 5M is a scientific approach that concists of observing, questioning, data collecting, associating, and communicating. This research uses classroom Action Research method which is designed by Stephen Kemmis dan Robyn Mc. Taggart that is acted in two cycles. Each cycle concists of planning, acting, observing, and reflecting. The result of the research shows that by using hypnotist balls, the students’ ordinal numbers reading increases 38,35%. The students’ learning activeness also increases 17.24%. Hypnotist balls in 5M helps the students’ learning process very much.